Efektivitas Strategi Pembelajaran Berbasis Masalah (PBL) Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa MIS Nurul Huda, Larangan Barat, Kamondung, Omben, Sampang - Nurul Qamariyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) strategy in enhancing students' critical thinking skills at MIS Nurul Huda, Larangan Barat, Kamondung, Omben, Sampang. The research method used is a quasi-experimental design with a pretest-posttest control group. The sample consisted of students from a specific class chosen through purposive sampling. Data were collected through critical thinking ability tests, observations, and interviews. The results show that the implementation of PBL significantly improved students' critical thinking skills. The average posttest score of students increased compared to the pretest, indicating that PBL can stimulate students to be more active in thinking, discussing, and finding solutions to the given problems. However, several factors such as students' prior knowledge and motivation also affect the effectiveness of PBL. The findings are expected to contribute to the development of learning strategies in similar schools.